Effects of using waste solid sheet photopolymer plates in combination with SBS on the rheological properties of bitumen - Kok, Baha Vural; Yetkin, Zulfu; Yalcin, Erkut (Taylor & Francis Ltd, 2023)
Large quantities of Solid Sheet Photopolymer plates (SSP) are used and wasted by the flexographic printing industry worldwide. The use of waste SSP, contains valuable polymers for bitumen modification, is an effective way of disposing of post-consumer products and an alternative way of obtaining new modifiers with good properties. Styrene-butadiene-styrene (SBS) copolymer, which is widely used in bitumen modification, causes excessive costs. The purpose of this study is to look at the effects of using SSP in combination with SBS and how much SSP saves on SBS content. Dynamic Shear Rheometer (DSR), Multi-Stress Creep Recovery (MSCR), Bending Beam Rheometer (BBR), Storage Stability tests, thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) were carried out. The performance of the 4 and 5 wt.% single SBS modifications was compared with the SBS + SSP combination. SBS and SSP additives were found to interact well, and the use of 7% SSP in combination with 2% SBS provided improved low and high temperature performance and storage stability compared to the single 5% SBS modification. The use of waste SSP, which is cheaper than bitumen, together with SBS in bitumen modification offers a cost-effective and environmentally friendly solution without compromising performance.
Keywords: Bitumen; modification; SBS; waste photopolymer plates; rheology